Environmental management of waste from laboratories at the Institute of Biological Sciences at the Federal University of Pará (Research, Society and Development, 2024)
The environmental management of waste in Federal Higher Education Institutions (IFES) is highly complex, in IFES the volume of waste generated is small, but with great diversity, which makes its treatment difficult. Specifically, waste generated in institutes requires reliable management methods. Activities with chemical, biological or infectious products have risks. The research is a case study at the Institute of Biological Sciences of the Federal University of Pará (ICB/UFPA), descriptive, empirical, using questionnaires applied to teaching staff and administrative technicians in education, with the aim of analyzing how these residues are managed. The results obtained showed that there is a lack of attention, lack of knowledge of legal standards, and deficiencies in information regarding the waste generated. It is concluded in this research that the ICB/UFPA lacks an Action Plan for the management of waste from laboratory services, the development of environmental education as an action tool, establishing target programs and activities for waste management and environment, defining a deadline for compliance, thus enabling greater security in the administration and management of its laboratories.